Dupuytren's Disease: Current State of the Art. (March 2014) - Henry, Mark
Background: This review article critically examines the current literature for Dupuytren's disease. Methods: Five procedures are considered: dermofasciectomy, limited fasciectomy, segmental aponeurectomy, needle aponeurotomy, and collagenase injection. Studies regarding the efficacy of these treatments focus primarily on the initial degree of correction, rate of recurrence, and complications. Results: No one treatment has been declared superior and substantial controversy exists. Comparison between studies has been hampered by the absence of uniform definitions for clinical success and measurable disease progression. Traditional postoperative care includes formal therapy and night splinting, but recent studies have questioned the value of these adjuncts. Conclusion: The extent of involvement at which the surgeon should intervene was previously well accepted by convention, but as the paradigm shifts towards less invasive procedures, treatment may be offered at an earlier stage. Future research should be structured to recognize the value-based decision making used by patients when selecting treatment.